LEGALIZATION OF ELECTRONIC BUSINESS CONTRACTS WITH THE USE OF ELECTRONIC STAMPS - Zetria Erma; Yulkarnaini Siregar; Pangeran (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Humans are social beings who really need other humans to fulfill various kinds of necessities of life, especially in the economic field. Technological developments have had a very large influence on legal relations in the economic field in society, where at first they were only carried out by individuals with the sole aim of fulfilling needs, turning into activities that are also carried out by groups to seek profit. These activities are known as business terms which include production, sales, purchases, exchange of goods and services and others. Business relations in modern society aim to exchange interests. Roscoe Pound provides a definition of "interest" or "interest" is "a demand or desire which human beings, either individually or through groups or associations in relations seek to satisfy" (interest as a demand or desire that humans want to satisfy, either individually or groups or associations). Through business relationships, the exchange of interests of the parties is always stated in the form of a contract considering that every step of business is a legal step (contract content). An important moment in the process of forming or closing an agreement is the meeting of wills, the interlocking of each statement of will as conveyed by one party to the other in a reciprocal manner and as understood by each of them.